Teachers' Attitudes towards Digital Game Based Assessment in English Language Teaching: A Mixed Methods Study - Hasna Sabila; Zakia Maulina (CV. Simpati Cloud, 2025)
This study explores teachers’ attitudes toward Digital Game-Based Assessment (DGBA) in English Language Teaching (ELT) using a mixed methods design. The integration of digital technology in education has encouraged innovative approaches to assessment, including game-based tools that enhance learning engagement. Teachers’ perceptions, however, determine the effectiveness of such implementations. Data were collected from 80 English teachers through questionnaires and semi-structured interviews. Quantitative data were analyzed statistically, while qualitative data were examined thematically. The results indicate that most teachers hold positive attitudes toward DGBA, perceiving it as an engaging and motivating assessment tool for students. Despite these positive views, several challenges were identified, including technical limitations, time management, and concerns about assessment validity. The study highlights the need for adequate training and institutional support to promote effective use of DGBA in language classrooms. The findings contribute to understanding how teachers can integrate technology-based assessments to enhance teaching and learning outcomes in ELT contexts.